Evolved pesticide tolerance in amphibians: Predicting mechanisms based on pesticide novelty and mode of action. (November 2015) - Hua, Jessica; Jones, Devin K.; Mattes, Brian M.; Cothran, Rickey D.; Relyea, Rick A.; Hoverman, Jason T.
Abstract: We examined 10 wood frog populations distributed along an agricultural gradient for their tolerance to six pesticides (carbaryl, malathion, cypermethrin, permethrin, imidacloprid, and thiamethoxam) that differed in date of first registration (pesticide novelty) and mode-of-action (MOA). Our goals were to assess whether: 1) tolerance was correlated with distance to agriculture for each pesticide, 2) pesticide novelty predicted the likelihood of evolved tolerance, and 3) populations display cross-tolerance between pesticides that share and differ in MOA. Wood frog populations located close to agriculture were more tolerant to carbaryl and malathion than populations far from agriculture. Moreover, the strength of the relationship between distance to agriculture and tolerance was stronger for older pesticides compared to newer pesticides. Finally, we found evidence for cross-tolerance between carbaryl and malathion (two pesticides that share MOA). This study provides one of the most comprehensive approaches for understanding patterns of evolved tolerance in non-pest species. Highlights: We explored patterns of tolerance to six insecticides across 10 wood frog populations. We found evidence that wood frogs have evolved tolerance to carbaryl and malathion. The likelihood of evolved tolerance was stronger for older compared to newer pesticides. We found evidence for cross-tolerance between carbaryl and malathion. This is one of the most comprehensive approaches studying evolved tolerance in a non-pest species. Abstract : Using 10 wood frog populations, we detected evidence for evolved tolerance, found that the evolved tolerance depends on insecticide novelty, and found evidence for cross-tolerance.